Pendampingan Pameran Edukatif “4 Anti” Sebagai Upaya Menumbuhkan Rasa Peduli dan Hormat pada Siswa SD Aisyiyah Jatinom: Pengabdian - Desy Anindia Rosyida; Ida Putriani; Muhammad Pramudya Riadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service (PkM) aims to strengthen the sense of care and respect in Aisyiyah Jatinom Elementary School students through the educational intervention of the "4 Anti" Exhibition (Anti-Sexual Violence, Anti-Bullying, Anti-Intolerance, and Anti-Corruption). The main problems identified are students' lack of understanding of complex social issues and the limited thematic learning media that raise these critical social values. In addition, there are teacher concerns in raising sensitive topics. The solutions offered include: (1) Teacher Workshops to increase capacity in "4 Anti" character education, (2) Student Mentoring through mini projects and thematic discussions, and (3) "4 Anti" Educational Exhibition as a place for character expression and campaign. The implementation method of this PkM uses a seminar approach, exhibition, and assistance in filling out understanding tests. The implementation stages consist of: (1) Preparation, (2) Seminar (providing knowledge about 4 Anti based on Canva), (3) Exhibition (students create and present 4 Anti campaign posters), (4) Assistance in filling out questionnaires, and (5) Evaluation. The evaluation will measure success based on the results of a student comprehension test on the "4 Antis" material. The targeted outcome is an article published in an accredited national journal. This Community Service Program (PKM) activity is expected to enrich students' character values ​​from a social and humanitarian perspective and strengthen the brand of a superior, friendly and critical school.